2020
DOI: 10.1016/j.seizure.2020.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the recurrence of convulsions with mild gastroenteritis in children

Abstract: To identify risk factors for the recurrence of convulsions with mild gastroenteritis (CwG) 1 in children. Methods: Altogether, 613 children with CwG admitted to Children's Hospital of Shanxi Province from January 2010 to December 2015 were selected, their clinical data were retrospectively analyzed, and patients were followed up for 4-10 years. Risk factors for the recurrence of CwG were analyzed based on the clinical characteristics of the children. Results: Relapse occurred in 35 patients (6.3 %). Recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
(32 reference statements)
4
13
1
Order By: Relevance
“…3 Previous studies conducted on the recurrence of CwG in children have reported a recurrence rate varying between 4.7 and 16.8%. 5,6,7,8 We found a recurrence rate of 4.9% in our study, indicating that the risk of CwG recurrence is still high. Hence, physicians should inform the parents at the onset about the recurrence risk of CwG to avoid panic.…”
supporting
confidence: 46%
See 3 more Smart Citations
“…3 Previous studies conducted on the recurrence of CwG in children have reported a recurrence rate varying between 4.7 and 16.8%. 5,6,7,8 We found a recurrence rate of 4.9% in our study, indicating that the risk of CwG recurrence is still high. Hence, physicians should inform the parents at the onset about the recurrence risk of CwG to avoid panic.…”
supporting
confidence: 46%
“…Similar findings were reported by Chen et al ., Shi et al . and Wang et al 3,6,7 . Hence, these studies had concluded that physicians should avoid extensive evaluations and long‐term anti‐epileptic treatment in children with CwG 3 .…”
Section: Risk Factors Non‐recurrence (N = 442) N (%) Recurrence (N = ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies in the past showed good prognosis of CwG, in recent years, with the increase in follow-up studies being conducted, it was found that children with CwG have some risk of seizure recurrence. Furthermore, if the age of seizure onset is ≤ 18 months and if there is a positive family history of epilepsy or febrile seizures, these children should be closely followed up within 6 -12 months from the first episode [17].…”
Section: Discussionmentioning
confidence: 99%